The impacts of word attack strategies in improving students’ reading skill: A sequential explanatory mixed methods study - Chanyalew Enyew Adamu(Ph.D.) (Bahir Dar Journal of Education, 2025)
This study sought to examine the effects of meaning and visual word attack instructional strategies on the reading skills of students focusing on Grade 6 students at one primary school in Bahir Dar City, Ethiopia. A sequential explanatory mixed-methods design was employed to explore the impact of these strategies on students' reading skills. A sample of 30 Grade 6 students was selected from an intact classroom using apurposive sampling technique. The students were assessed using a pre-test-post-test design, with the pre-test administered before the intervention and the post-test administered after the intervention. The results showed that the word attack instructional strategies significantly improved students' reading skills, as measured by a paired samples t-test.Furthermore, the qualitative results revealed improvements in students' self-confidence, motivation, and participation in reading activities. The findings suggest that incorporating word attack strategies into reading lessons can have a positive impact on students' reading skills and overall reading experiences